2016
DOI: 10.3346/jkms.2016.31.12.1983
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Trial of the Efficacy and Tolerability of Neoadjuvant Sunitinib for Inoperable Metastatic Renal Cell Carcinoma

Abstract: This study aimed to evaluate the efficacy, safety, and tolerability of 2-cycled neoadjuvant sunitinib therapy (NST) in patients with inoperable metastatic renal cell carcinoma (mRCC). Between 2009 and 2012, 14 patients with inoperable mRCC from 5 Korean academic centers were prospectively enrolled after collecting their clinicopathological data and completing health-related questionnaires. The best overall response (BOR), safety profile, and changes in quality of life during NST were assessed using the RECIST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Chang et al9 suggested that among patients with RCC, the genotype of cyclooxygenase 2 (COX2) could be used as a novel marker for the diagnosis of RCC. In 14 patients with inoperable mRCC, neoadjuvant sunitinib therapy showed a satisfactory response rate although a small number are operable after treatment 10. It has been indicated that among Chinese patients with mRCC, both sorafenib and sunitinib are effective agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al9 suggested that among patients with RCC, the genotype of cyclooxygenase 2 (COX2) could be used as a novel marker for the diagnosis of RCC. In 14 patients with inoperable mRCC, neoadjuvant sunitinib therapy showed a satisfactory response rate although a small number are operable after treatment 10. It has been indicated that among Chinese patients with mRCC, both sorafenib and sunitinib are effective agents.…”
Section: Discussionmentioning
confidence: 99%
“…In 14 patients with inoperable mRCC, neoadjuvant sunitinib therapy showed a satisfactory response rate although a small number are operable after treatment. 10 It has been indicated that among Chinese patients with mRCC, both sorafenib and sunitinib are effective agents. The median OS of patients treated with the two agents is similar (24.0 vs 24.0 months; P = 0.298), while the mPFS with sorafenib is higher compared with sunitinib (11.1 vs 10.0 months; P = 0.028).…”
Section: Discussionmentioning
confidence: 99%